1998
DOI: 10.1901/jeab.1998.70-235
|View full text |Cite
|
Sign up to set email alerts
|

Control by Sample Location in Pigeons' Matching to Sample

Abstract: Three experiments assessed the impact of sample location in pigeons' matching to sample. Experiments 1 and 2 demonstrated that after line or hue identity matching was acquired to high levels of accuracy with center-key samples, varying sample location across the three keys disrupted performances. The drop in accuracy occurred following both zero-delay and simultaneous training and was mostly confined to trials in which the sample appeared on a side key. Experiment 3 attempted to diminish control by location by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
99
5
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 17 publications
(37 reference statements)
2
99
5
9
Order By: Relevance
“…These results are less surprising, however, on the assumption that in the absence of any special training (Lionello-DeNolf & Urcuioli, 2000), a visual stimulus appearing at one location is a functionally different stimulus for pigeons than the same stimulus appearing at another location (Lionello & Urcuioli, 1998). From this perspective, the left-versus right-sample contingencies for location-relevant group were not conflicting.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These results are less surprising, however, on the assumption that in the absence of any special training (Lionello-DeNolf & Urcuioli, 2000), a visual stimulus appearing at one location is a functionally different stimulus for pigeons than the same stimulus appearing at another location (Lionello & Urcuioli, 1998). From this perspective, the left-versus right-sample contingencies for location-relevant group were not conflicting.…”
Section: Discussionmentioning
confidence: 84%
“…Previous research has shown that location is a controlling feature of the nominal conditional and discriminative stimuli in tasks such as matching-to-sample (Iversen, 1997;Iversen, Sidman, & Carrigan, 1986;Lionello & Urcuioli, 1998). For instance, Lionello and Urcuioli (1998) trained pigeons to high levels of accuracy on twosample, two-comparison matching tasks with a typical configuration of stimuli: samples on the center key and comparison stimuli on the adjacent (left and right) side keys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…É provável que o estabelecimento de relações de controle de estímulo incoerentes com o planejamento experimental, como relatado aqui, explique boa parte dos resultados inconsistentes já obtidos em trabalhos buscando a demonstração de identidade generalizada (Iversen, 1997) e a formação de classes de equivalência em não-humanos e humanos com desenvolvimento severamente atrasado (Devany, Hayes, & Nelson, 1986;Lionello & Urcuioli, 1998;Lionello-DeNolf & Urcuioli, 2002;Sidman & cols., 1982).…”
Section: Discussionunclassified
“…A interferência do controle não programado pela posição dos estímulos já foi claramente documentada em procedimentos de treino de relações condicionais com sujeitos não-humanos (Iversen, 1997;Iversen, Sidman, & Carrigan, 1986;Lionello & Urcuioli, 1998;Sidman, 1992). Usualmente, um treino de emparelhamento ao modelo por identidade ocorre com o estímulo modelo sendo apresentado numa janela central e dois estímulos de comparação em duas janelas laterais.…”
unclassified